2017
DOI: 10.28945/3670
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Knowledge-based Framework for Social and Metacognitive Support in Mobile Learning

Abstract: Aim/Purpose: This work aims to present a knowledge modeling technique that supports the representation of the student learning process and that is capable of providing a means for self-assessment and evaluating newly acquired knowledge. The objective is to propose a means to address the pedagogical challenges in m-learning by aiding students’ metacognition through a model of a student with the target domain and pedagogy. Background: This research proposes a framework for social and meta-cognitive support to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…This study confirms that subjective cognitive load is mainly associated with the achievement of educational goals in the contexts of distance learning (Zhampeissova et al, 2020). The cognitive load has been recognised as a significant factor that influences achievement results in the digital environment learning processes (Al- Hunaiyyan et al, 2017). This study's observed results could be attributed to the idea that educational programs in a remote learning environment are more effective if the cognitive load is optimal (Curum & Khedo, 2020).…”
Section: Discussionmentioning
confidence: 75%
“…This study confirms that subjective cognitive load is mainly associated with the achievement of educational goals in the contexts of distance learning (Zhampeissova et al, 2020). The cognitive load has been recognised as a significant factor that influences achievement results in the digital environment learning processes (Al- Hunaiyyan et al, 2017). This study's observed results could be attributed to the idea that educational programs in a remote learning environment are more effective if the cognitive load is optimal (Curum & Khedo, 2020).…”
Section: Discussionmentioning
confidence: 75%
“…The purpose of the adaptive feedback algorithm is to determine the appropriate feedback for different students based on adaptive characteristics [23]. The input to the adaptive feedback algorithm is the partial problem solving state P S s .…”
Section: A Adaptive Feedback Algorithmmentioning
confidence: 99%
“…The cognitive approach places a student and internal mental processes at the center of learning. Due to the fact that cognitivism seeks to identify various processes associated with the acquisition of knowledge and thus to provide strategies that support student learning, educators can use cognitive approaches to help students effectively achieve their educational goals [20].…”
Section: -65 66 -80 81 -100mentioning
confidence: 99%
“…Distance learning complicates the assessment process and forces educational institutions to consider the technical aspects of mobile learning, social norms, and pedagogical theories, including learning strategies, learning outcomes, engagement, and collaboration. Therefore, the development and implementation of mobile learning technologies should be integrated with traditional education aspects to ensure the sustainability of the learning system on mobile basis [20].…”
Section: -65 66 -80 81 -100mentioning
confidence: 99%